RISK FACTORS IN THE PERSISTENCE OF CERVICAL INTRAEPITHELIAL LESIONS ASSOCIATED WITH LOW-RISK HPV INFECTION AFTER TREATMENT ABLACTIVO - Genaro, Vega-Malagon; Guadalupe, Zaldivar- Lelo De Larrea; Carlos, Sosa-Fereyra; Hernan, Del Valle-Jimenez; Javier, Avila-Morales; Alma, Becerril-Santos; Jesus, Vega-Malagon A. (European Scientific Journal, ESJ, 2014)
General Objective Determine the risk factors in the persistence of cervical intraepithelial lesions of high and low risk associated with HPV infection ablactivo posttreatment. Methodology. - Cases and controls, cases were 40 women with persistent cervical intraepithelial lesions ablactivo posttreatment. The controls 80 women with healing at 6 months after treatment were analyzed sociodemographic variables, reproductive, sexual, abuse, nutritional and associated comorbidity. The analysis was performed using odds ratios, confidence interval 95%, x2 test, Student t test. Results. - The factors that showed statistically significant difference (p <0.05) were: Extension of the lesion greater than 2 cm2. (OR 8.53), presence of associated pathology. (OR 6.97), smoking associated with alcoholism (OR 5.40) Three or more sexual partners in the past three years. (O.R. 5.25), Obesity. (OR 4.58), Husband uncircumcised (OR 3.45), Home less sexually active at 17 years (OR 2.77), More than two periods (average) annual sexually transmitted infections in the last three years (OR 2.53 ), the pathology associated with the group of patients who continued the lesion were cervicovaginal infection and obesity. Conclusion. - It is important to identify factors that may cause persistence of lesions to perform a more effective treatment